Crime, Justice and COVID-19 - Ainslie, Sam; Brown, Tom; Carnighan, Maureen; Case, Stephen; Case, Stephen; Coxhead, John; Forder, Phil; Fowler, Andrew; Fowler, Rachel; Haines, Abbie; Hamilton, Ian; Hampson, Kathy; et al. (Policy Press, 2023)
This edited collection offers the first system-wide account of the impact of COVID-19 on crime and justice in England and Wales. It provides a critical discussion of the challenges faced by criminal justice agencies (prison, probation, youth justice, courts, police), professionals and service users in adapting to the extraordinary pressures of the pandemic on policy, practice and lived experience. The text integrates first-hand narrative and artistic accounts from a variety of key stakeholders experiencing the Criminal Justice System (CJS). The editors recommend a range of evidence-based policy and practice improvements, not only in terms of planning for future pandemics, but also those that will benefit the CJS and its stakeholders in the longer term.